Publicaciones periódicas de la Red Nacional de los Ferrocarriles Españoles, RENFE (1941-2005) - López Hernández, Alfonso (Documentación de las Ciencias de la Información, 2009)
This paper provides an overview of periodical publications issued by RENFE throughout its lifetime (1941-2005), and by its heirs RENFE Operadora and ADIF after 2005. Most of these official publications fall under two categories: Journals and magazines aimed at external communication and relations; and those directed at serving the needs of RENFE’s numerous workers and their families.
Keywords: RENFE; Railway Publications